Direct Utilization of Geothermal Energy - John W. Lund (Energies, 2010)
The worldwide application of geothermal energy for direct utilization is reviewed. This paper is based on the world update for direct-use presented at the World Geothermal Congress 2010 in Bali, Indonesia (WGC2010) [1] which also includes material presented at three world geothermal congresses in Italy, Japan and Turkey (WGC95, WGC2000 and WGC2005). This report is based on country update papers prepared for WGC2010 and data from other sources. Final update papers were received from 70 countries of which 66 reported some direct utilization of geothermal energy for WGC2010. Twelve additional countries were added to the list based on other sources of information. The 78 countries having direct utilization of geothermal energy, is a significant increase from the 72 reported in 2005, the 58 reported in 2000, and the 28 reported in 1995. An estimate of the installed thermal power for direct utilization at the end of 2009, reported from WGC2010 is 48,493 MWt, almost a 72 % increased over the 2005 data, growing at a compound rate of 11.4% annually with a capacity factor of 0.28. The thermal energy used is 423,830 TJ/year (117,740 GWh/yr), about a 55% increase over 2005, growing at a compound rate of 9.2% annually. The distribution of thermal energy used by category is approximately 47.2% for ground-source heat pumps, 25.8% for bathing and swimming (including balneology), 14.9% for space heating (of which 85% is for district heating), 5.5% for greenhouses and open ground heating, 2.8% for industrial process heating, 2.7% for aquaculture pond and raceway heating, 0.4% for agricultural drying, 0.5% for snow melting and cooling, and 0.2% for other uses. Energy savings amounted to 250 million barrels (38 million tonnes) of equivalent oil annually, preventing 33 million tonnes of carbon and 107 million tonnes of CO2 being release to the atmosphere which includes savings in geothermal heat pump cooling (compared to using fuel oil to generate electricity).